Greening cities – To be socially inclusive? About the alleged paradox of society and ecology in cities. (June 2017) - Haase, Dagmar; Kabisch, Sigrun; Haase, Annegret; Andersson, Erik; Banzhaf, Ellen; Baró, Francesc; Brenck, Miriam; Fischer, Leonie K.; Frantzeskaki, Niki; Kabisch, Nadja; Krellenberg, Kerstin; Kremer, Peleg; et al.
Abstract: Greening cities, namely installing new parks, rooftop gardens or planting trees along the streets, undoubtedly contributes to an increase in wellbeing and enhances the attractiveness of open spaces in cities. At the same time, we observe an increasing use of greening strategies as ingredients of urban renewal, upgrading and urban revitalization as primarily market-driven endeavours targeting middle class and higher income groups sometimes at the expense of less privileged residents. This paper reflects on the current debate of the social effects of greening using selected examples. We discuss what trade-offs between social and ecological developments in cities mean for the future debate on greening cities and a socially balanced and inclusive way of developing our cities for various groups of urban dwellers. We conclude that current and future functions and features of greening cities have to be discussed more critically including a greater awareness of social impacts.